Sports and school involvement and performance: a systematic review of literature - Porto Maciel, Larissa Fernanda; Oliveira Farias, Gelcemar; Dallegrave, Eduardo José; Flach, Mônica Cristina; Do Nascimento, Juarez Vieira; Folle, Alexandra (Retos (Madrid), 2023)
The purpose of this article was to map the published empirical investigations on the involvement and sports and school performance of young athletes, through a systematic literature search in the Lilacs, ProQuest, Scielo and SportDiscus electronic databases. The characteristics of the studies were analyzed using absolute frequency, while their results were analyzed using categories (NVIVO PRO, version 12). The 17 selected studies revealed, in the athletes' perception, more benefits than harms due to the involvement with the sport, a positive relationship between sport and study, and a positive influence of sports practice on the academic performance of student-athletes. It can be concluded that the dual career accumulates numerous commitments and obligations, however, the benefits and positive relationships established make this involvement, in the perception of young people, something favorable to their development, making it essential to their human formation in a comprehensive way. Further research is needed to broaden the understanding of how trainings are related and how they influence the lives of student-athletes throughout their lives. Key Words: Athlete, Students, Education, Youth Sport.